PENGGUNAAN ELECTRONIC-DEWEY DECIMAL CLASSIFICATION (E-DDC) DALAM MANAJEMEN PERPUSTAKAAN KOMUNITAS DI KABUPATEN BARRU - Andi Risfan Rizaldi; Asriani Hasan (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Tanah Laut (Politala), 2021)
Barru Membaca is a community library that provides community library services in Barru Regency. As the number of library collections and members increases, two fundamental problems are encountered, namely the difficulty of managing library collections due to the non-existent classification system and the difficulty of managing members who carry out library transactions. This Community Service (PKM) activity aims to provide skills for partners to use the Dewey Decimal Classification (DDC) library classification system and integrate it with information technology using the Senayan Library Management System (SLiMS) software. This activity contains material on the DDC system and the practice of using SLiMS. The output of this activity is the implementation of training on the use of Electronic-Dewey Decimal Classification (E-DDC), which two lecturers facilitate from the Faculty of Economics and Business, Universitas Muhammadiyah Makassar, as implementers and assist my students as assistants. There were ten participants, consisting of the Barru Membaca manager and the local community. As a result of this activity, participants understood the DDC concept as a library material classification system and were able to apply SliMS software in managing library collections.